(Non‐)Insurance Markets, Loss Size Manipulation and Competition: Experimental Evidence*. (9th November 2020) - Hinloopen, Jeroen; Soetevent, Adriaan R.
Abstract : The common view that insurer buyer power may effectively counteract provider market power critically rests on the idea that consumers and insurers have a joint interest in pushing for price and cost reductions. We develop theory and provide experimental evidence that the interests of insurers and consumers may be misaligned when insurers have the power to influence the service supplier's cost. Insurers with such buyer power may benefit from increasing initial loss sizes to create demand for insurance. Insurer competition eliminates their profits but markets do not return to the initial non‐insurance state. This constitutes a welfare loss.